TIME-DEPENDENT MODELS OF U-TH-HE AND K-AR EVOLUTION AND THE LAYERING OF MANTLE CONVECTION - Albarede F. (My University, 1998)
High-resolution seismic tomography indicates that lithospheric plates penetrate the 670 km discontinuity. A common view holds that the isotopic composition of He and Ar is incompatible with geophysical evidence because (a) the inventory of terrestrial radiogenic argon requires that the lower mantle is largely undegassed, and (b) recycling of outgassed lithospheric material should destroy the primitive isotopic composition of helium and argon in the lower mantle. It is first shown, however, that the `argon problem' results from the assumption that the terrestrial K/U ratio is ≥1.2#104, a value that cannot be taken for granted. In addition, earlier geochemical models of steady-state He and Ar cycles are shown to be inadequate, because common concepts of residence time do not apply to multiple reservoir systems. A time-dependent model with four reservoirs (lower and upper mantle, crust, atmosphere) is evaluated in which elemental fractionation upon transfer and variable growth rate for crustal growth, atmosphere extraction, and lithosphere production are taken into account. Vigorous lithosphere production early in the history of the Earth enhances the degassing of the upper mantle in agreement with the very radiogenic character of 4He/3He and 40Ar/36Ar ratio in mid-ocean ridge basalts. Recycling of oceanic lithosphere stripped of its rare gases, but also of its U, Th, and K, into the lower mantle preserves the primitive isotopic signature of the rare-gas inventory of this reservoir. Accumulation in the lower mantle of ancient plates essentially barren of U, Th, and K, but nevertheless showing isotopic evidence of plate-tectonic processes in the less incompatible elements (Nd, Hf, Sr), can account for the isotopic composition of rare gases in hot-spot basalts. The outgassed character of the upper mantle was probably acquired during the early Archaean when mantle activity was intense and is still being enhanced by the fluxing of K, U, and Th from the descending lithospheric plates. The view of the mantle offered by seismic tomography is therefore not incompatible with the isotopic evidence provided by terrestrial rare gases.
Keywords: MANTLE CONVECTION; RARE GASES; BOX MODELS; MANTLE GEOCHEMISTRY; GEOCHEMICAL DYNAMICS; MANTLE TOMOGRAPHY